2021
DOI: 10.3390/ijms22042128
|View full text |Cite
|
Sign up to set email alerts
|

Non-Musculoskeletal Benefits of Vitamin D beyond the Musculoskeletal System

Abstract: Vitamin D, a fat-soluble prohormone, is endogenously synthesized in response to sunlight or taken from dietary supplements. Since vitamin D receptors are present in most tissues and cells in the body, the mounting understanding of the role of vitamin D in humans indicates that it does not only play an important role in the musculoskeletal system, but has beneficial effects elsewhere as well. This review summarizes the metabolism of vitamin D, the research regarding the possible risk factors leading to vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 300 publications
0
22
0
2
Order By: Relevance
“…Vitamin D is highly important for bone health and mineral metabolism, but more recently interest has been driven by its non-musculoskeletal functions. Vitamin D deficiency is linked with numerous illnesses, including osteoporosis and osteomalacia, autoimmune disorders, infectious diseases, muscle weakness and falls, cardiovascular diseases (CVDs), cancers, and neurological disorders [ 1 ]. The vitamin D status in the body is mainly dependent on the exposure to ultraviolet (UV) light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D is highly important for bone health and mineral metabolism, but more recently interest has been driven by its non-musculoskeletal functions. Vitamin D deficiency is linked with numerous illnesses, including osteoporosis and osteomalacia, autoimmune disorders, infectious diseases, muscle weakness and falls, cardiovascular diseases (CVDs), cancers, and neurological disorders [ 1 ]. The vitamin D status in the body is mainly dependent on the exposure to ultraviolet (UV) light.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the main source of vitamin D3 occurs via skin exposure to UV light from the sun rather than by food intake. Vitamin D production is initiated in the skin by UVB with the conversion of 7-dehydrocholesterol into pre-vitamin D3 in the skin, followed by two successive hydroxylations in the liver, to produce 25-hydroxycholecalciferol [25(OH)D] and then in the kidneys to produce the active metabolite, 1,25-dihydroxycholecalciferol [1,25(OH)2D]. Dietary intake of vitamin D, mainly from fish oils, fish, egg yolks, and to a lesser extent mushrooms, and from dietary supplements, accounts for a small amount of the daily vitamin D requirement.…”
Section: Introductionmentioning
confidence: 99%
“…As a member of secosteroid hormones, vitamin D plays essential roles in both calcium and phosphorus metabolism, cell proliferation and differentiation, muscle contraction, nerve transmission, and function of the immune system [12]. Due to the immunomodulatory, anti-inflammatory, antifibrotic, and antioxidant roles of vitamin D, its deficiency has associations with several diseases including obesity, diabetes, cardiovascular diseases, bone metabolic disorders, cancers, neuropsychiatric disorders and autoimmune diseases, and more recently with increased risk of SARS-CoV-2 infection [12][13][14]. The link between VDD and the risk of cardiometabolic diseases has been extensively studied [15][16][17], and it has been shown that vitamin D exhibits anti-adipogenic activity in 3T3-L1 preadipocytes [18,19] and has potential roles in inducing the expression of the insulin receptor, in the regulation of insulin secretion, glucose homoeostasis, and inflammation [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Загалом, дефіцит вітаміну D визнаний гло бальною проблемою охорони здоров'я, оскіль ки на нього страждає більшість світового насе лення [83].…”
unclassified
“…Хоча метаболіт 25 OH D не має фізіологічної функції, його широко використо вують як показник для визначення рівня віта міну D у людини, оскільки відображає надхо дження вітаміну D з їжею та ендогенний синтез, а також тому, що він є основною формою цирку ляції вітаміну D із тривалим періодом напівви ведення (2-3 тижні). На противагу цьому, 1α,25 (OH)2 D, як активна форма, не є зручним показником для оцінювання загального рівня вітаміну D в організмі, оскільки він має корот кий період напіввиведення (<4 год) [83].…”
unclassified